2019
DOI: 10.1016/s2213-2600(19)30081-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI for lung cancer staging: a step in the right direction

Abstract: We declare no competing interests. 1 Wenzel SE. Asthma phenotypes: the evolution from clinical to molecular approaches. Nat Med 2012; 18: 716-25. 2 Boudier A, Chanoine S, Accordini S, et al. Data-driven adult asthma phenotypes based on clinical characteristics are associated with asthma outcomes twenty years later. Allergy 2018; published online Dec 13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The prompt diagnosis and staging of NSCLC provides vital information on the anatomical details and extent of cancer with respect to the size of the primary tumor, lymph nodal status, and the presence or absence of metastasis in distant organs, which can guide more assertive therapeutic decisions [ 30 , 31 ]. The National Comprehensive Cancer Network and European Society of Medical Oncology recommend an intravenous contrast agent-enhanced chest CT, 18-fluorodeoxyglucose ([18F]-FDG)-PET-CT and, depending on the guidelines, a brain MRI for staging of NSCLC before treatment with curative intent [ 32 , 33 , 34 ]. MRI was found to be typically used for diagnosis in most countries unless contraindications to this procedure exist.…”
Section: Discussionmentioning
confidence: 99%
“…The prompt diagnosis and staging of NSCLC provides vital information on the anatomical details and extent of cancer with respect to the size of the primary tumor, lymph nodal status, and the presence or absence of metastasis in distant organs, which can guide more assertive therapeutic decisions [ 30 , 31 ]. The National Comprehensive Cancer Network and European Society of Medical Oncology recommend an intravenous contrast agent-enhanced chest CT, 18-fluorodeoxyglucose ([18F]-FDG)-PET-CT and, depending on the guidelines, a brain MRI for staging of NSCLC before treatment with curative intent [ 32 , 33 , 34 ]. MRI was found to be typically used for diagnosis in most countries unless contraindications to this procedure exist.…”
Section: Discussionmentioning
confidence: 99%
“…Several radiological screening techniques, including chest x-ray, computed tomography (CT) scan of the chest and thorax, bronchoscopy, ultrasound of the chest and lungs, magnetic resonance imaging (MRI), and positron emission tomography (PET), have been used to aid the diagnosis of lung cancer in HIC countries, through the detection of suspicious lesions and sampling of mediastinal lymph nodes [21][22][23][24][25]. Lung biopsies are obtained by bronchoscopy and surgical procedures for histopathological analysis and appraisal.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete resection is complete tumor resection under the naked eye, but there are still residues under the light microscope. Complete resection is the complete tumor resection under the naked eye, and there is no residue under the light microscope [5]. Studies reported that the 5-year survival rate of patients with early lung cancer after surgical treatment was 45-65% and that of patients with advanced lung cancer after nonsurgical treatment was 5-10% [6][7][8].…”
Section: Introductionmentioning
confidence: 99%